PENERAPAN METODE WEIGHTED PRODUCT UNTUK PENENTUAN PENERIMA BANSOS KEPADA MASYARAKAT TERDAMPAK COVID-19 - Dian Permata Sari (Teknik Informatika, 2021)
Since Covid 19 attacked Indonesia, almost all sectors have been affected. In the education sector, which requires students to study from home (online), in the economic sector the poverty rate is getting higher, many workers have been laid off and some are sent home. The face of the Indonesian economy has become a mess. One of the ways for the government to reduce the impact of the COVID-19 pandemic is to provide social assistance to the community. However, in distributing aid, the distributors are often constrained in prioritizing the recipient community. The mechanisms for distributing aid are complicated and often not well targeted due to inappropriate criteria for beneficiaries and inaccurate / inaccurate data. So that not a few people protested because they did not receive assistance even though they were also affected by the Covid 19 pandemic. The decision support system using the weighted product method was considered capable of finding the highest priority for beneficiaries based on predetermined criteria, namely employment status, home status, domicile, dependents. and income per month. The final result is a rating of vactor V where the alternative which has the highest value has the highest priority to receive assistance.